Antimicrobial Resistance and Biofilms Underlying Catheter-Related Bloodstream Coinfection by Enterobacter cloacae Complex and Candida parapsilosis - Štefánek, Matúš (2022)
This article belongs to the Special Issue Microbial Biofilms, Antimicrobials, and Virulence Determinants.